Dictamnine promotes apoptosis and inhibits epithelial-mesenchymal transition, migration, invasion and proliferation by downregulating the HIF-1α and Slug signaling pathways. (25th December 2018) - Wang, Jing Ying; Wang, Zhe; Li, Ming Yue; Zhang, Zhihong; Mi, Chunliu; Zuo, Hong Xiang; Xing, Yue; Wu, Yan-Ling; Lian, Li-Hua; Xu, Guang Hua; Piao, Lian Xun; Ma, Juan; et al.
Abstract: Dictamnine (DTM) is a natural alkaloid isolated from the root of Dictamnus dasycarpus Turcz and has been shown to exhibit multiple biological functions, including anti-inflammatory, antifungal, anti-angiogenic and anticancer activity. However, the mechanisms by which dictamnine inhibits tumor growth are not fully understood. In this study, we investigated the effectiveness of dictamnine as a treatment for cancer and to identify the underlying mechanisms of its anticancer activity. Here, dictamnine showed the potent inhibitory activity against HIF-1α and Slug activation induced by hypoxia in various human cancer cell lines. This compound markedly decreased the hypoxia-induced accumulation of HIF-1α and Slug protein in a dose-dependent manner. Further analysis revealed that dictamnine inhibited HIF-1α protein synthesis, without affecting its degradation. Our results demonstrated that dictamnine reduced HIF-1α protein synthesis by downregulating the mTOR/p70S6K/eIF4E and MAPK pathways, and reduced the expression of Slug by inhibiting the GSK-3β/Slug signaling pathway. Moreover, epithelial-mesenchymal transition (EMT) was inhibited in dictamnine-treated tumors by downregulation of HIF-1α and Slug, as reflected by the upregulation of E-cadherin and Occludin, and the downregulation of N-cadherin and Vimentin. Phenomenological experiments showed that dictamnine reduced migration and invasion, inhibited HCT116 cell proliferation and promoted HCT116 cell apoptosis by downregulating HIF-1α and Slug. In vivo studies further confirmed that dictamnine treatment caused significant inhibition of tumor growth in a xenograft tumor model. These findings suggest that dictamnine is a potent cancer inhibitor, providing a rationale for anticancer pathway-targeted therapy. Highlights: Dictamnine decreased the hypoxia-induced HIF-1α and Slug protein. Dictamnine downregulating the mTOR/p70S6K/eIF4E, MAPK, and GSK-3β/Slug pathways. Dictamnine inhibited EMT markers by downregulating HIF-1α and Slug. Dictamnine inhibited migration, invasion, proliferation and promoted apoptosis. Dictamnine may be a potential therapeutic agent for inhibiting cancer progression.